The effect of embryo transfer using abdominal and vaginal ultrasound methods on pregnancy outcome: a retrospective cohort study - Samira Azimi; Shahrzad Zadeh Modarres; Zahra Heidar; Tayebeh Esfidani (Mashhad University of Medical Sciences, 2023)
Introduction: Abdominal ultrasound (TAUS) and transvaginal ultrasound (TVUS) are used in IVF/ICSI methods to transfer the embryo into the uterine cavity. Since these methods have limitations, the present study was conducted with aim to compare them and their effect on pregnancy outcome. Methods: This retrospective cohort study was conducted in 2018-2022 on 522 intracytoplasmic sperm injection cycles in the Fertility Unit of Mahdieh Hospital in Tehran. After reviewing the files, the patients were divided into two groups of embryo transfer with transvaginal and abdominal ultrasound. After collecting demographic information, pregnancy outcomes including chemical pregnancy and clinical pregnancy, abortion under 10 weeks, ectopic pregnancy and the duration of embryo transfer were compared in the two groups. Data analysis was done using SPSS statistical software (version 26) and Mann-Whitney and Pearson Chi-square tests. P<0.05 was considered significant. Results: The frequency of chemical and clinical pregnancy and abortion was higher in the TAUS group, however, the incidence of EP was higher in the TVUS group (p>0.05). Also, the duration of embryo transfer using TAUS was longer compared to TVUS, but it was not statistically significant (p>0.05). The number of transferred embryos was equal in both groups, but the number of 5-day embryos was higher in the TAUS group, which was statistically significant (p<0.05). Conclusion: There was no difference between abdominal ultrasound and transvaginal ultrasound in terms of pregnancy outcomes.